Implementation of the Internal Control System in Increasing the Accountability of the Financial Reports - Budi Raharjo; Aris Sarjito; Editha Praditya Duarte (PT FORMOSA CENDEKIA GLOBAL, 2024)
his study aims to describe the implementation of the internal control system in increasing the accountability of the financial statements of the Ministry of Defense of the Republic of Indonesia. This research uses a qualitative method with a descriptive analysis approach. Data was collected by interview method based on the maturity assessment of the integrated Government Internal Control System. The results of this study indicate that the Ministry of Defense has implemented an adequate internal control system. In line with this, there is also an increase in the accountability of its financial statements